Analysis Of Factors Affecting Fiscal Stress In Local Goverments (Case Studies in Districts Kunci Bersama Areas for the Period of 2015 - 2019) - Neni - Nurhayati (Universitas Kuningan, 2020)
ABSTRACTThis study aims at determining the effect of local revenue and capital expenditure on Fiscal Stress in the Kunci Bersama Area in 2015-2019. The population of this study is the district/city government in the Kunci Bersama Area. The entire population becomes a sample called the saturated sample (census). This study has 45 data observations derived from 9 districts/cities' financial statements for the 2015-2019 period. The data used in this study is secondary data in the form of a Budget Realization Report in the Kunci Bersama Areas for the 2015-2019 Period. The hypothesis testing tool in this study is the Eviews 9 software. From the test results, it is found that local revenue and capital expenditure affect fiscal stress. Local revenue has a negative effect on fiscal stress, while capital expenditure positively affects fiscal stress.